2022
DOI: 10.1177/17562864221140180
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of gait independence using the Trunk Impairment Scale in patients with acute stroke

Abstract: Background: Gait recovery is one of the primary goals of stroke rehabilitation. Gait independence is a key functional component of independent activities in daily living and social participation. Therefore, early prediction of gait independence is essential for stroke rehabilitation. Trunk function is important for recovery of gait, balance, and lower extremity function. The Trunk Impairment Scale (TIS) was developed to assess trunk impairment in patients with stroke. Objective: To evaluate the predictive vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…The novelty of this study lies in the focus on trunk stability in subacute stroke patients along with lumbar BMD. TIS scores in the early stages of stroke have usually been considered a predictor of functional ambulation at discharge [ 39 ]. In addition, our findings indicate that an early assessment of trunk balance could predict lumbar spine BMD in patients with trunk instability.…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of this study lies in the focus on trunk stability in subacute stroke patients along with lumbar BMD. TIS scores in the early stages of stroke have usually been considered a predictor of functional ambulation at discharge [ 39 ]. In addition, our findings indicate that an early assessment of trunk balance could predict lumbar spine BMD in patients with trunk instability.…”
Section: Discussionmentioning
confidence: 99%
“…Walking speed was measured by a stopwatch marking when the patient passed the start and end lines of a 10-m walkway. In P1, some extent of recovery was observed regarding the weakness of her right lower extremity (from the FMA-LE score of 15-23, cutoff point: 21 [16] ) and trunk function (from the TIS score of 10-20, cutoff: 12 [17] ) over a 2-months period following her admission. The improvement in her balance performance stalled (from the Mini-BESTest score of 4-15, cutoff: 17.5 [18] ), but she was able to walk independently on an even floor at discharge (FAC score improvement from 0-4).…”
Section: Clinical Evaluationsmentioning
confidence: 99%
“…The associated factors were based on published studies. We used age, leg strength, sitting balance, cognitive function, urinary function, and ADL independence [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The four variables of leg strength, sitting balance, cognitive function, and urinary incontinence were dichotomized, as previously described [26].…”
Section: Outcome and Associated Variablesmentioning
confidence: 99%
“…Previous longitudinal studies of walking dependence and walking speed in stroke have only reported associations in terms of odds ratios and other measures [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Since it is clear that the strong associations captured by odds ratios do not translate into predictive ability in treating speci c patients, there is a need to use statistical methods focused on predicting outcomes for speci c individuals and to demonstrate the discrimination and calibration of prediction models [6, [21][22][23].…”
mentioning
confidence: 99%
See 1 more Smart Citation